Remoção de bactérias e genes de resistência a antibióticos em estações de tratamento de águas residuais urbanas - Grehs, Bárbara Werle Nunes (2019)
The spread of antibiotics bacterial resistance is a subject of great concern for public and environmental health, caused mainly by the indiscriminate use of antibiotics and the incorrect discard of medicines. In this context, Wastewater Treatment Plants (WWTP) are a particular point of interest, because they act as reservoirs for antibiotic resistant bacteria (ARB) and antibiotic resistance genes (ARG), which subsequently release high loads of bacterial resistance on the waterbodies receptors. The recognition that the WWTPs act with selective pressures on the microorganisms and favor the horizontal transfer of genes, increasing the abundance of resistance genes, causes seizure. Based on the current state of the art, this study concludes that improvements in wastewater treatment technologies are necessary, not only in the removal of solids, nutrients and organic matter, but also in the removal of residues of resistant antibiotics and microorganisms. The main goal of this work was to evaluate the aggregation capacity, with aluminum sulfate and tannin, to reduce the ARB and ARG loading in treated urban effluents from an Urban Waste Water Treatment Plant (UWWTP), as well as, verify the impact of the treatment on the structure and diversity of the bacterial community and evaluate the ability to reactivate the microorganisms after storage period. It was noticed that both coagulants reduced the prokaryotic organisms loading, including ARB, however only aluminum sulphate was effective in the removal of analyzed ARGs. Also, both coagulants promoted changes in the bacterial community compared to uncoagulated effluent.